Parent-young communication on sexual and reproductive health issues and its associated factors: experience of students in Agaro Town, Ethiopia - Daba Abdissa; Workitu Sileshi (BMC, 2023)
Plain English summary Sexual and reproductive health (SRH) is at the base of young people's living and wellbeing. A significant number of young peoples are affected by avoidable SRH problems. Parent-young communication on SRH is critical in informing them about risk and protective behaviors which in turn decrease the likelihood of involvement in risky sexual behaviors. This study was intended to assess this issue on students learning at Agaro town, Ethiopia during April 13 to April 20, 2019 using pretested interviewer-administered structured questionnaire with sample size of 315. The study finding showed that 61.3% of the participants were discussed on SRH issues with their parents. According to multivariable logistic regression analysis educational status of parents, having family size of < 5 and boy/girlfriend were significantly associated with parent adolescent communication. Cultural taboos, shame and parents lack of knowledge were the major barriers for communication. Thus, it is necessary to educate students and parents to address the identified problems thereby prevent young population from risky sexual behaviors.